Pronunciation Anxiety, Pronunciation-Related Views and Pronunciation Learning Actions of EMI and English Major Students - Esther Gómez Lacabex; Hanne Roothooft (Research in Language)
The present study explored pronunciation views, learning actions and anxiety in two differentiated English learner groups: one group which was studying English in an engineering degree and another group enrolled in an English major degree. The results from a questionnaire and focus group sessions revealed that the groups share some views such as a wish to improve their English pronunciation and adherence to native pronunciation references as well as pronunciation learning actions such as watching series or talking to native speakers. However, we also observed significant differences between the groups as the English major students tended to view pronunciation learning as a discipline, while the engineering students saw it as a communicative skill. The English majors also exhibited more pronunciation anxiety, specifically fear of ridicule and worry of making mistakes. They also revealed more anxiety-related themes in the focus group discussions such as worry about their pronunciation, pronunciation shame or unease because they do not know how to pronounce a word or cannot understand. Finally, the English major group was also more demanding of lecturers’ accurate pronunciation. These results suggest that differences regarding English pronunciation anxiety between different learner profiles may need to be considered during their English language learning progress.